Effects of Left and Right Pneumonectomy on Time- and Frequency-Domain Parameters of Heart Rate Variability - Amar, D. (Institutional Knowledge at Singapore Management University, 1999)
Morbid cardiac events after pneumonectomy have been attributed to autonornic mechanisms. Analysis of heart rate variability (HRV) offers a noninvasive technique to assess modulation of sympathetic and parasympathetic activity. There is little data available on the systematic changes in time- and frequency-domain parameters of HRV in response to pneumonectomy and cardiac plexus neural trauma.